Wild Boar (Sus scrofa L.) as the Biomonitor of Cadmium and Lead Pollution in the Republic of North Macedonia - Cokoski, Kristijan; Beuković, Dejan; Maletić, Vladimir; Polovinski Horvatović, Miroslava; Vukadinović, Marko; Dimitrieska Stojković, Elizabeta; Enimiteva, Vangelica (Hrvatski Sumarski Institut (Croatian Forest Research), 2023)
Until the outbreak of African swine fever in almost the entire Europe and consequently in the Republic of North Macedonia (2022), the population of wild boars was in increase. The biological characteristics of this species make it suitable to be used as a bioindicator for environmental pollution. The concentrations of cadmium and lead (Cd and Pb) were measured using atomic absorption spectrophotometry in the liver of free ranging wild boars. Samples were taken from 608 animals, harvested in a period of 7 years (2016-2022), in 11 hunting locations that cover the whole territory of the Republic of North Macedonia. The mean value of Pb in the liver in all hunting areas was 0.225 mg·kg-1 wet weight with range of 0.154-0.722 mg·kg-1, while mean Cd was 0.366 mg·kg-1 and ranged from 0.177 to 0.464 mg·kg-1. A statistically significant difference in Cd was found between the hunting locations, while Pb differed between hunting years. The mean Cd concentrations were significantly higher in Pelagonisko, Krivorečansko and Ohridsko-Prespansko hunting areas than in those from Pološko hunting area, while the mean Pb values in 2019 and 2020 were significantly higher than the mean value determined in 2021. For Cd, 18.2% of the total number of samples exceeds the maximum allowed limit provided in the legislation, while for Pb it was 6.7%. The maximum mean value for Pb (0.336 mg·kg-1) was measured in 2020 and for Cd (0.449 mg·kg-1) in 2016. The mean values for Pb and Cd obtained in this study were in line with data reported for wild boar from other European countries.
Keywords: wild boar; Pb; Cd; liver; hunting areas; pollutants